(untitled) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2014)
The entire financial system is at the service of a sustainable productive economy over time. When this does not occur, bubbles arise. The term “bubble” refers to a situation in which excessive future expectations cause asset prices to rise far above their fundamentals. The goal of this article is describe the bubbles that led to the current financial crisis in order to raise awareness of their negative effects on society.The negative effects of their out bursts require from the central bank to take measuresto avoid bubbles in the future. Some of these measures are suggested in this article.